Socio-Demographic and Clinical Profile of Children with Epilepsy: A Cross-sectional Study - Anny, Munmun Sultana; Mahmud, Md Asif; Alam, Syeda Tabassum (Journal of Bangladesh College of Physicians and Surgeons, 2026)
Background: Epilepsy is a common neurological disorder with the most demanding and challenging management, It ranges from narrowly focused medication-based management to holistic management. Martial and Methods: This cross-sectional study was conducted from Jan 2020 to June 2020 at the Institute of Pediatric Neurodisorder and Autism, Bangabandhu Shiekh Mujib Medical University (BSMMU). Previously diagnosed and purposively selected 70 epilepsy patients who are attending at the outpatient department during data collection period were included in the study. Data was collected through face-to-face interview using a pre tested questionnaire. Results: Mean age of the children was 4.28±3.65 (SD) years, majority were male (75.70%) having middle class group (54.73%) with rural inhabitant (51.40%). More than half (51.40%) parents had superstitious belief and 48.60% had history of taking consultation from traditional healer. History of post-natal complication and developmental delay prominent among patients and 47.1% had the onset of the disease within 06 months of age. One-fourth (24.3%) patients able to live independently without any supervisions. Nearly half of the patients (47.2%) had focal seizure and 37.1% had generalized seizure. Conclusion: In Bangladesh perspective, superstitious belief and seeking consultation to traditional healers are major drawbacks for availing modern treatment options. Mean age of the epileptic children was 4 years with clear male preponderance. Focal seizure was the commonest type among the study patients. It is also revealed that adequate treatment enabled a good number of patients to live independently. J Bangladesh Coll Phys Surg 2026; 44: 88-93